Analisis Pola Makan terhadap Status Gizi Anak Usia Prasekolah di TK X - Sulistyorini, Suci (Masker Medika, 2021)
Introduction : WHO data shows that cases of underweight pre-school children in the world were 15.7% and overweight preschoolers were 6.6% (WHO, 2013). Based on the 2018 Riskesdas data, the prevalence of stunting in children under five was 30.8.% Decreased compared to the 2013 Riskesdas data, which was 37.2%. Meanwhile, South Sumatra Province for the prevalence of stunting in toddlers based on Riskesdas in 2018 also decreased when compared to the results of the Riskesdas in 2013 from 36.7% to 32.0%. However, the prevalence of stunting was still high when compared to the WHO standard, which was <20% (South Sumatra Provincial Health Office, 2020). The purpose of this study was to determine the relationship between diet and nutritional status of preschool children in Kindergarten X. Method: The research design used analytical survey method with cross sectional research design. The research instrument used a food recall form questionnaire and measurement of height and weight. The population in this study were all students of Kindegarten X totaled 35 respondents. Sampling technique with total sampling. The analysis used univariate and bivariate with the Chi-Square test. Result: Based on the univariate analysis, it was found that 68.6% of good children's diet, 31.4% of bad diet, 60% normal nutritional status, 25.7% thin, and 14.3% fat. The results of the Chi-Square statistical test showed that the relationship between diet and nutritional status of preschool children in Kindergarten X with p value 0.002. Conclusion : that the relationship between diet and nutritional status of preschool children in Kindergarten X.